A Comparative Study of Laparoscopic Appendectomy Specimen Retrieval Using Plastic Endo-Bag versus Direct Removal through 10mm Umbilical Port - Yaswanth Sandeep S; Vrvld pratyusha (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Acute appendicitis is one of the most common surgical emergencies, often managed by laparoscopic appendectomy due to its advantages of less postoperative pain, faster recovery, and shorter hospital stay compared to open surgery. However, the optimal technique for specimen retrieval—whether using a plastic Endo Bag or direct extraction through the umbilical port—remains debated, particularly regarding infection prevention and operative efficiency. Aim: To compare two techniques of laparoscopic appendectomy specimen retrieval—Plastic Endo Bag Method and Direct Retrieval through the 10 mm Umbilical Port—in terms of clinical characteristics, mean operation time, specimen extraction time, first passage of flatus, and length of hospital stay. Materials and Methods: A prospective observational study was conducted in the Department of General Surgery at a tertiary care hospital, involving 50 patients diagnosed with acute appendicitis. Participants were alternately allocated into two equal groups: Group A (Endo Bag retrieval) and Group B (Direct umbilical port retrieval). Operative time, extraction time, postoperative recovery parameters, and surgical site infections were recorded and statistically analyzed, with p < 0.05 considered significant. Results: Of the 50 patients studied, the majority were between 21–30 years of age with nearly equal gender distribution. Mean operation and specimen extraction times were significantly shorter in Group B compared to Group A (p < 0.05 and p < 0.001, respectively). The first passage of flatus occurred on postoperative day one in most patients, and the mean hospital stay was similar in both groups. Although port-site infections were slightly more frequent in Group B, the difference was not statistically significant (p = 0.157). Conclusion: Direct umbilical port retrieval of the appendix reduced operative and extraction times without adversely affecting postoperative recovery when compared to Endo Bag use. While Endo Bag retrieval may offer a marginal reduction in wound contamination risk, both techniques demonstrated comparable clinical outcomes.